2016
DOI: 10.1039/c6dt03436e
|View full text |Cite
|
Sign up to set email alerts
|

Spin crossover and reversible single-crystal to single-crystal transformation behaviour in two cyanide-bridged mixed-valence {FeIII2FeII2} clusters

Abstract: The reactions of tricyanometallate precursors, (PhPMe)[(Tp)Fe(CN)·0.5CHCN] (1) (Tp = tri(4-methyl-pyrazol-1-yl)borate) and (NBu)[(Tp)Fe(CN)] (Tp = methyltris(pyrazolyl)borate) with the presence of the tetradentate tpa ligand (tpa = tris(2-pyridylmethyl)amine) and Fe(ClO)·6HO afford two new cyano-bridged mixed-valence {FeFe} molecular squares: [(Tp)Fe(CN)][Fe(tpa)]·2ClO·HO (2·HO) and [(Tp)Fe(CN)][Fe(tpa)]·2ClO·CHOH (3·CHOH). Solvent-exchange compounds of 3·CHOH, [(Tp)Fe(CN)][Fe(tpa)]·2ClO·2HO (3·2HO), and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…At 250 K, the 57 Fe Mössbauer spectrum of solid 2 shows a high-spin Fe­(II) species comprising 46(5)% of the sample with an isomer shift (δ) of 0.880(9) mm/s and quadrupole splitting (Δ E Q ) of 3.22(2) mm/s (Figure A, green). , The remaining sample has a broad, poorly resolved signal (blue) potentially composed of multiple sites with an δ of 0.23(2) mm/s and Δ E Q of 0.81(2) mm/s which we assign as low-spin Fe­(II) sites. These parameters are outside of the typical ranges for both low-spin Fe­(II) (δ: 0.36–0.52 mm/s; Δ E Q : 0.23–0.52 mm/s) and low-spin Fe­(III) (δ: 0.20–0.28 mm/s; Δ E Q : 1.5–1.7 mm/s) reported for TPA ligated 6-coordinate complexes but are similar to other low-spin Fe­(II) species …”
Section: Results and Discussionmentioning
confidence: 99%
“…At 250 K, the 57 Fe Mössbauer spectrum of solid 2 shows a high-spin Fe­(II) species comprising 46(5)% of the sample with an isomer shift (δ) of 0.880(9) mm/s and quadrupole splitting (Δ E Q ) of 3.22(2) mm/s (Figure A, green). , The remaining sample has a broad, poorly resolved signal (blue) potentially composed of multiple sites with an δ of 0.23(2) mm/s and Δ E Q of 0.81(2) mm/s which we assign as low-spin Fe­(II) sites. These parameters are outside of the typical ranges for both low-spin Fe­(II) (δ: 0.36–0.52 mm/s; Δ E Q : 0.23–0.52 mm/s) and low-spin Fe­(III) (δ: 0.20–0.28 mm/s; Δ E Q : 1.5–1.7 mm/s) reported for TPA ligated 6-coordinate complexes but are similar to other low-spin Fe­(II) species …”
Section: Results and Discussionmentioning
confidence: 99%
“…For SCO complexes, an abrupt spin transition at room temperature with a wide hysteresis is one of the most important requirements from the viewpoint of applications . Currently, it is still a great challenge to design and prepare systems that exhibit SCO around room temperature. , In 2008, Gao et al reported an Fe­(II) SCO complex of tridentate pyridyl aroylhydrazones with the transition temperature ( T c ) of room temperature . Subsequent research indicates that Fe­(II) pyridyl aroylhydrazones are good candidates for high T c SCO materials .…”
Section: Introductionmentioning
confidence: 99%
“…[11] Nevertheless, an increasing number of interesting examples of Prussian blue molecular polymetallic assemblies have been reported due to the fact that they usually exhibit both optical and magnetic bistability which arises from a reversible metal-to metal charge transfer between the Co III (or Fe III ) and the Fe II centres. This family of compounds include pentanuclear trigonal bipyramidal{Fe II 2 /Fe III 3 } and {Fe II 2 /Co III 3 }units, [12,13] octanuclear cubic{Fe II /Fe III } 4 and {Fe II /Co III } 4 assemblies, [14,15] homonuclear {Fe II /Fe III } 2 squares, [16,17] and a significant number of heterotetranuclear square complexes {Fe II /Co III } 2 . [11,18,19] Recently, we have reported the preparation of the diamagnetic cyanido-bridged [{Co III {(Me) 2 (µ-ET)cyclen}} 2 {(µ-NC) 2 Fe II (CN) 4 } 2 ] 2square complex [20] via a mechanistically designed self-assembly reaction (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%